Agenda setting: probing the issues during the 13th general election - Syed Abdullah Idid, Syed Arabi (UKM Press, 2017)
This study discusses the development of agenda setting and its application in political communication especially in general elections in Malaysia. The vast majority of studies on Agenda Setting have found widespread support for a media influence on issue salience despite studies used different methodologies and issues. The theory postulates that people were simply led to think about the agenda as set by the media. The salience of the media agenda would then be reflected as the people agenda, measured through rank correlation. With the emergence of technologies, questions arise among scholars about whether the theory on Agenda Setting would remain viable in later years and whether people would continue to obtain their news from a given number of media outlets, given the range of new media channels being made available over the years. The discussion of this study contributes to a better understanding of agenda setting in current Malaysian media landscape.